2014
DOI: 10.1177/1548051814527771
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Leadership Behaviors Predict Changes in Job Satisfaction and Well-Being in Low-Skilled Workers

Abstract: About 16% of the German workforce is low skilled (Lyly-Yrjänäinen, 2008), including formally qualified employees who work in positions that do not require formal training. These educated employees in the low-skilled workforce are often immigrants with meager German language skills or workers who lack an occupational qualification that is accepted in Germany. Therefore, low-skilled workforces are characterized by a high proportion of immigrant workers (Hoppe, 2011;Seebaß & Siegert, 2011). On the other hand, wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 95 publications
(128 reference statements)
4
21
0
Order By: Relevance
“…De Lange and colleagues (De Lange, Taris, Kompier, Houtman, & Bongers, ) have argued that specifically for investigating effects of change in social support, shorter time lags of approximately 6 months are more suitable. Indeed, among a sample of immigrant and native employees in Germany, there were effects of change in supervisor support on change in job satisfaction and work‐related affective well‐being over a 6‐month period (Winkler, Busch, Clasen, & Vowinkel, ). When approaching time lags of 1 year, change in supervisor support no longer affected change in performance‐related outcomes (Li, Fay, Frese, Harms, & Gao, ).…”
Section: Discussionmentioning
confidence: 99%
“…De Lange and colleagues (De Lange, Taris, Kompier, Houtman, & Bongers, ) have argued that specifically for investigating effects of change in social support, shorter time lags of approximately 6 months are more suitable. Indeed, among a sample of immigrant and native employees in Germany, there were effects of change in supervisor support on change in job satisfaction and work‐related affective well‐being over a 6‐month period (Winkler, Busch, Clasen, & Vowinkel, ). When approaching time lags of 1 year, change in supervisor support no longer affected change in performance‐related outcomes (Li, Fay, Frese, Harms, & Gao, ).…”
Section: Discussionmentioning
confidence: 99%
“…Given this evidence, the current study hypothesizes that perceived management support will be positively related to PsyCap (Hypothesis 3). It should be noted that the causal directionality in this proposed relationship is debatable; it is plausible that employees who enjoy high levels of wellbeing are more likely to perceive their leaders as supportive (Nielsen et al, 2008;Winkler, Busch, Clasen, & Vowinkel, 2015). While there is likely some level of mutual reinforcement between PsyCap and perceived managerial support, previous research has established that perceptions of supervisors have a causative effect on employees' psychological capital and job performance (Rego et al, 2012).…”
Section: Psychological Capitalmentioning
confidence: 95%
“…Supervisors' support in low-skilled occupations tends to be a major predictor of employees' well-being (Ariza-Montes, Arjona-Fuentes, Han, & Law, 2018;Winkler, Busch, Clasen, & Vowinkel, 2015). Nevertheless, SAS is distinct from supervisors' support, as SAS specifically enhances employees' sense of autonomy through autonomy-supportive behaviours, therefore giving a more precise indicator of the type of supervision which contributes to the well-being of employees in low-skilled occupations.…”
Section: Psychological Autonomy a Basic Need As Proposed By Self-detmentioning
confidence: 99%
“…Nevertheless, SAS is distinct from supervisors' support, as SAS specifically enhances employees' sense of autonomy through autonomy-supportive behaviours, therefore giving a more precise indicator of the type of supervision which contributes to the well-being of employees in low-skilled occupations. Winkler et al (2015) called for future studies to train supervisors in low-skilled occupations on being supportive to improve employees' well-being. Relatedly, autonomysupportive training studies have shown the positive effect of the training on supervisors and employees' well-being (Deci, Connell, & Ryan, 1989;Hardré & Reeve, 2009).…”
Section: Psychological Autonomy a Basic Need As Proposed By Self-detmentioning
confidence: 99%